(untitled) (Al-Aasar, 2025)
This article explores the Islamic concept of reverence for sacred papers (Awrāq-e-Muqaddasah) — documents that contain Qur’anic verses, Prophetic sayings (Ahādīth), the names of Allah, and other religious texts. Drawing from Qur’anic injunctions, Prophetic traditions, the opinions of the four major schools of Islamic jurisprudence, and examples from the lives of the pious predecessors, it establishes that physical and spiritual purity is essential for touching and handling such sacred materials. The article also highlights the contemporary challenges and widespread negligence in respecting these sacred items, including their misuse in households, improper disposal, and digital-era violations such as carrying Qur’an apps into impure places. The study stresses the urgent need for public awareness, institutional responsibility, and practical mechanisms to ensure the sanctity of sacred texts is upheld. Ultimately, the paper argues that revering these sacred documents is not only a matter of legal obligation but a profound expression of faith and devotion that brings about spiritual elevation and divine favor.